Implementing a reverse logistics system: a case study. (27th May 2009) - Rubio, Sergio; Miranda, Francisco J.; Chamorro, Antonio; Valero, Victor
This paper is based on the results of a research project developed in an important Spanish industrial group to analyse if a reverse logistics system can be implemented in some of its companies. The business activity of this group is focused on the steel industry and the aim of the project was to design and evaluate a recovery system for packaging materials used for galvanised steel coils. Up to now, this type of packaging is disposed of because the current structure of the packaging system is not appropriate from a reverse logistics point of view. For this reason, we propose a new packaging system that can be recovered through a reverse logistics system generating economic and environmental advantages.